ALLERGIC CONTACT CHEILITIS DUE TO LIPSTICK - Kus Harijanti; Yoli Sidharta Santosa (Odonto : Dental Journal, 2016)
Allergic contact cheilitis is a common cause inflammation of the outer lip or vermillion margin. It is due to a type IV hypersensitivity reaction following contact with an allergen. Allergic contact cheilitis is more common in women than men. Lip cosmetics are the most common allergen source in women, while toothpastes allergy occur mostly in men. Purpose: To report the management of allergic contact cheilitis due to lip cosmetics. Case : A 22-years old woman complaint was dryness of the lips, cracking and peel off after using lip cosmetics since one week ago. Patient used new lips-cosmetics two weeks ago. No history to atopic allergy and no medication. Intra oral examination was normal. Management : patient was advised to avoid wearing lip-cosmetics. To relieve symptoms were given topical anti-inflammation non steroids, multivitamin and maintain to oral hygiene. Patient revered to patchtesting. Patient had strongly positive result to the tested lip cosmetics. Patient were given topical anti inflammation steroids and from dermatology department were given antihistamine tablets. Conclusion : Patch testing is the key to this diagnosis and for determining of contact allergen.